Patient-related barriers to cancer pain management – a prospective cross sectional study in a tertiary hospital. - Choy, YC; Wan Nuruddin Shah WJ; Wong, YM; Boey, CY; Noor Zuhaily, MN; Kumutha, T; Juliana, J (Department of Surgery, UKM Medical Centre, 2013)
Effective management of cancer pain is often hampered by patients’ lack of knowledge regarding cancer pain management and other barriers related to ethnicity and religious beliefs. This cross sectional study was performed to determine the patient-related barriers to effective cancer pain management. One hundred patients receiving cancer pain management were studied. Inclusion criteria were: patients over the age of 18 years, able to communicate, with known diagnosis of cancer, experiencing persistent pain for the past two weeks. A modified version of the Barriers Questionnaire II (BQ-II) was used and a modified Brief Pain Inventory was used to assess the pain profile. Barriers such as, patient’s attitude and beliefs, communication skills and fear of side effects of pain medication were determined, given a score and the summation was recorded as the total patient related barriers score. Overall, 85% of respondents achieved more than 40% pain relief and the 72 of 100 patients reported low patient related barrier scores of 6 or less. Nevertheless, the main patient related barriers were: fear of tolerance to opioids (51%), ethnicity (p=0.003) and religious beliefs (p=0.002) which constituted the major components of the patient-related barriers score. Ethnicity and religious beliefs had significant influence on patient-related barriers score suggesting the need of further investigation into this area. In order to achieve a comprehensive view, other barriers to effective cancer pain management such as those related to the health systems and healthcare providers need to be assessed together.